Al-Yasār al-Islāmī: Iṭlālah ‘Āmmah - Naṣr Abū Zaid (Al-Jami'ah Research Centre, 2004)
Islamic thought develop rapidly as the progress of Islam in the classical era especially when Islam facing modernity nowadays. In general, the discourse of Islamic thought ranges from the “left” to the “right”. The term